FREQUENCY OF MICROALBUMINURIA IN TYPE II DIABETES MELLITUS PATIENTS: A CROSS SECTIONAL STUDY - SAJJAD, J; WAHAB, S; HIDAYAT, S; ZAHID, U; ABDULLAH , HA; MUSHEER, Z (Biological and Clinical Sciences Research Journal, 2024)
Microalbuminuria is an early marker of diabetic nephropathy and an important predictor of cardiovascular and renal complications in patients with Type II diabetes mellitus. Identifying its prevalence and associated risk factors is crucial for early intervention Objective: The objective of this study was to determine the frequency of microalbuminuria and its associated risk factors in patients with Type II diabetes mellitus. Methods: This cross-sectional study was carried out in the medical ward of a tertiary care hospital from March 2024 to September 2024. Two hundred fifty patients, aged 30 years or older, diagnosed with Type II diabetes, were selected. The presence of microalbuminuria was assessed using urine albumin-to-creatinine ratio measurements. Results: Mean age was 52.04 ± 12.311 years, gender-wise there were 152 males (60.8%) and 98 females (39.2%) patients. The frequency of microalbuminuria was 76 (30.4%). Microalbuminuria was notably associated with BMI, duration of diabetes, and the presence of hypertension, with significant associations observed (p < 0.05) for all these factors. Conclusion: Our study demonstrated that microalbuminuria was found in 30.4% of patients presenting with diabetes type II, with significant associations observed for hypertension, BMI, and the duration of diabetes.